Pengelompokkan Provinsi di Indonesia Berdasarkan PDRB atas Dasar Harga Konstan Tahun 2013 - Lembang, Ferry Kondo; Lessil, Patresya Yulita; Aulele, Salmon Notje (Jurnal Matematika; Vol 7 No 2 (2017)DO - 10.24843/JMAT.2017.v07.i02.p84, 2017)
Regional gross domestic product is one of the important indicators to determine economic conditions in an area. Therefore it is very interesting to discuss and to determine the economic progress of a region. Cluster anlysis aims to classify objects based on the characteristics into cluster that have the properties that are relatively similar and clearly distinguish between one cluster agains another. The main objective of the research that classifies 33 provinces based on the value of regional gross domestic product at constant price in 2013 using hierarchical cluster analysis for average linkage method. The results showed that the cluster were carried out on 33 provinces in Indonesia formed 3 cluster with details of that cluster 1 consisting of Sumatera, Kalimantan, Sulawesi, Nusa Tenggara, Bali, Papua, Maluku and Jawa Tengah, DI Yogyakarta, and Banten, cluster 2 consisting of 1 provinces of DKI Jakarta and cluster 3 which consists of 2 provinces namely Jawa Barat dan Jawa Timur.